Making a case for just agricultural transformation in the UNFCCC: An analysis of justice in the Koronivia Joint Work on Agriculture - Sarku, Rebecca; Tauzie, Mapenzie; Whitfield, Stephen (Frontiers in Sustainable Food Systems, 2023)
Introduction From 2018 to 2022, the Koronivia Joint Working Group on Agriculture (KJWA) was the key forum for debating global agricultural change and integrating agricultural transformation priorities into the mechanisms of the United Nations Framework Convention on Climate Change (UNFCCC). As a forerunner to the landmark decision at COP27 to initiate the Sharm El-Sheik Joint Work on Implementation of Climate Action on Agriculture and Food Security, it provided an opportunity to further the (as yet underdeveloped) discourse around social transformation and just transformation in agriculture. At the conclusion of this 4 year process, we ask: to what extent and in what ways has a just agricultural transformation been envisioned within the Koronivia Joint Working Group on Agriculture and what are the implications for the Sharm El-Sheik Joint Work on Implementation? Methods The paper presents a textual analysis of 155 written submissions, workshops, and concluding statements from across the full programme of KJWA workshops, meetings, and consultations. Results We find that references to just transformations in agriculture within KJWA are largely implicit, but not absent. We argue that justice has been most obvious and evident when it comes to discussion about who is (and where are) the most vulnerable to climate change and variability, and how access to climate smart technologies and information is distributed. Less evident have been discussions about just representation in the governance and visioning of agricultural transformation, and there have been few explicit appeals to address the historical injustices that have shaped agricultural and rural livelihoods in the Global South. Discussion We argue that following its conclusion, there is a danger that the outcomes of KJWA become reduced to a focus on the scaling up of a techno-centric vision of agricultural transformation. To counter this, there is need for ongoing dialogue to develop a shared and more complete understanding of justice that should be central to how agricultural transformation is integrated into the UNFCCC. We highlight some recommendations of how a justice agenda could be taken forward under the Sharm El-Sheik Joint Work on Implementation.